The Impact of Parking Policy on House Prices - Jesper de Groote; Jos van Ommeren; Hans R.A. Koster (Tinbergen Institute, 2017)
Paid parking is the recommended policy tool by economists to deal with excess demand for street parking. However, we know very little about the effects of this policy on residents. This is particularly important in the context that residents have political power and usually vote against paid parking when it is detrimental to residents. Hence, in our analysis, we take into account that residents receive residential parking permits which provides political support for paid parking. We estimate the combined effect of a paid-parking parking policy – i.e. the introduction of paid parking and residential parking permits on residents – by examining its effect on house prices. We focus on Amsterdam and Utrecht using data over a period of 30 years. We do not find any effect of this paid-parking policy on house prices. This finding is consistent with the idea that residents only vote in favor of a local policy when it has no negative impact on their house prices.
Keywords: R20; R40; 330; parking; parking policy; hedonic price analysis